Informal urban settlements, adverse weather events and adaptation : responses to incidents of flash flooding by residents in Eerste Fabriek, Mamelodi - Thebe, Vusilizwe (University of Pretoria, 2025)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2024.